Economics, private and public choice - Gwartney, James D. (Academic Press, 1976)
Economics: Private and Public Choice is an aid for students and general readers to develop a sound economic reasoning. The book discusses several ways to economic thinking including six guideposts as follows: (i) scarce goods have costs; (ii) Decision-makers economize in their choices; (iii) Incentives are important; (iv) Decision-makers are dependent on information scarcity; (v) Economic actions can have secondary effects; and (vi) Economic thinking is scientific. The book explains the Keynesian view of money, employment, and inflation, as well as the monetarist view on the proper macropolicy.